2014
DOI: 10.1371/journal.pone.0094706
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of a Complex Industrial Effluent by Biosorbents Derived from Freshwater Macroalgae

Abstract: Biosorption with macroalgae is a promising technology for the bioremediation of industrial effluents. However, the vast majority of research has been conducted on simple mock effluents with little data available on the performance of biosorbents in complex effluents. Here we evaluate the efficacy of dried biomass, biochar, and Fe-treated biomass and biochar to remediate 21 elements from a real-world industrial effluent from a coal-fired power station. The biosorbents were produced from the freshwater macroalga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 42 publications
(50 reference statements)
1
30
0
Order By: Relevance
“…Biochar produced from freshwater macroalgae can also be used as a biosorbent that effectively binds metals [35,36]. Alternatively, the biomass can be treated with an iron (Fe) solution prior to conversion to biochar to produce a biosorbent that effectively binds metalloids [35][36][37].…”
Section: Biosorbentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Biochar produced from freshwater macroalgae can also be used as a biosorbent that effectively binds metals [35,36]. Alternatively, the biomass can be treated with an iron (Fe) solution prior to conversion to biochar to produce a biosorbent that effectively binds metalloids [35][36][37].…”
Section: Biosorbentsmentioning
confidence: 99%
“…Alternatively, the biomass can be treated with an iron (Fe) solution prior to conversion to biochar to produce a biosorbent that effectively binds metalloids [35][36][37]. The sequential application of biochar and Fe-treated biochar can then be used to comprehensively remove metals and metalloids from a range of industrial wastewaters [36].…”
Section: Biosorbentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential of seaweeds as biosorbents for removal of heavy metal has been studied by various scientists in recent years offers continuous availability and reusability of sorbent in numerous cycles. Brown and green seaweeds are studied most for the biosorption research [16] [17]. Nasab et al, 2017 [18] reported 53 to 80 % of metal removal efficiency for 0.1 to 0.5 g/l of biomass of Gracillaria corticata.…”
Section: Int J Adv Res 5(8) 923-939mentioning
confidence: 99%